The Role of Psychological Training in The Formation of Students' Personality - Klicheva Zulfiya Polatovna (Genius Journals, 2021)
This article presents the results of a study of the problem of organizing psychological training with students, as well as interpersonal relationships arising in the process of communication.
Keywords: Psychological preparation; personality; interpersonal relations; communication